O assédio moral no Brasil e a aplicabilidade da Convenção 190 da Organização Internacional do Trabalho - Tirapelle, Renatta Souza Carvalho (2024)
This dissertation addresses workplace bullying and its combat considering the ILO Convention 190, analyzing the implementation of this norm in Brazil and its effectiveness in promoting safer and more respectful work environments. The general objective was to analyze the implementation of this convention at the national level and evaluate its effectiveness in combating workplace bullying. To this end, the following specific objectives were outlined: to examine the conceptualization and historical evolution of the recognition of workplace bullying; to investigate the impacts of workplace bullying on the health and well-being of workers; to analyze the incorporation of Convention 190 into the Brazilian legal system; and to identify and compare international approaches to combating workplace bullying. The methodology adopted was qualitative in nature, involving both bibliographic review and national and international document analysis. The bibliographic review included the analysis of academic literature, ILO reports, and other relevant sources on workplace harassment and human rights. The document analysis focused on Brazilian and international legislation, particularly Convention 190. The findings showed that the implementation of Convention 190 has the potential to significantly transform the fight against workplace harassment in Brazil, fostering safer and more respectful work invironments. It concluded that aligning national laws with foreign standards is crucial for worker protection, highlighting the need for corporate policies and continuous training to prevent harassment.